Development of Islamic-Based Sex Education Module for Students - Yuliana, Yuliana; Afrinaldi, Afrinaldi (Journal La Sociale, 2025)
Article entitled Development of Islamic-Based Sex Education Module for Students at SMP IT Madani Payakumbuh, by Yuliana NIM 20122014. The researcher is interested in taking this title because parents, children and teachers are currently facing serious challenges due to the rampant free sexual behavior and sexual violence against children. Children are not only victims, but also perpetrators of these conditions. The lack of knowledge of children about sex and low awareness of correct sexual behavior is caused by the absence of information from families and schools. This study aims to develop an Islamic-based sex education module so that children can recognize and protect themselves to avoid free sex behavior and sexual violence. The research conducted is an educational design research (EDR) with the Plomp development model. The test instrument was validated by 3 validators and 2 validators for practicality. Field tests were conducted on 50 students of SMP IT Madani Payakumbuh. The construct validity data analysis technique uses Aiken V. The results obtained from construct validity are 0.92 for the content aspect with very high validity, 0.72 for the media aspect with high validity, 0.89 for the language aspect with very high validity. The results obtained for practicality are 93.33 with a very practical value. The results of the field trial are 86.00 with a very effective category. Based on the data obtained, the developed module has been valid, practical and effective to use.